2006
DOI: 10.1002/glia.20453
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α/IFN‐γ‐induced iNOS expression increased by prostaglandin E2 in rat primary astrocytes via EP2‐evoked cAMP/PKA and intracellular calcium signaling

Abstract: Astrocytes, the most abundant glia in the central nervous system (CNS), produce a large amount of prostaglandin E(2) (PGE(2)) in response to proinflammatory mediators after CNS injury. However, it is unclear whether PGE(2) has a regulatory role in astrocytic activity under the inflamed condition. In the present work, we showed that PGE(2) increased inducible nitric oxide synthase (iNOS) production by tumor necrosis factor-alpha and interferon-gamma (T/I) in astrocytes. Pharmacological and RNA interference appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…In the CNS, however, selective EP2 activation reduces microglial migration toward injured tissue (39), whereas ablation of the EP2 receptor limits lipopolysaccharideinduced, microglia-mediated inducible nitric oxide synthase (iNOS) production and neurotoxicity in mixed cortical cultures (40). As the resident forms of macrophages in the brain, microglia appear to play a pivotal role in seizure-induced immune responses because activated microglia are a major source of a host of proinflammatory and neurotoxic factors including cytokines, chemokines, free radicals, and prostanoids in injured neuronal tissues (41,42); activated astrocytes might also contribute to brain inflammation by producing iNOS in response to EP2 activation (43). Our work shows that an EP2 receptor antagonist significantly reduced the seizuremediated induction of seven cytokines and chemokines, among them IL-1β and IL-6, and also blunted the induction of activated glial markers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, however, selective EP2 activation reduces microglial migration toward injured tissue (39), whereas ablation of the EP2 receptor limits lipopolysaccharideinduced, microglia-mediated inducible nitric oxide synthase (iNOS) production and neurotoxicity in mixed cortical cultures (40). As the resident forms of macrophages in the brain, microglia appear to play a pivotal role in seizure-induced immune responses because activated microglia are a major source of a host of proinflammatory and neurotoxic factors including cytokines, chemokines, free radicals, and prostanoids in injured neuronal tissues (41,42); activated astrocytes might also contribute to brain inflammation by producing iNOS in response to EP2 activation (43). Our work shows that an EP2 receptor antagonist significantly reduced the seizuremediated induction of seven cytokines and chemokines, among them IL-1β and IL-6, and also blunted the induction of activated glial markers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Moriya et al (39) have demonstrated that the expression of GFAP in SCN was dramatically changed under constant lighting conditions, while that was not constant under a light-dark cycle. Another study has suggested that alteration of GFAP expression might reflect activity of astrocytes (41), indicating the possibility that circadian rhythms of GFAP expression are correlated with those of astroglial functions. Glutamate transporter EAAT2 has also been proposed as a candidate for regulation by astrocyte circadian rhythms (4).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the induction of COX-2 itself can reduce surrounding NO levels through the ability of NO to act as a co-substrate for its peroxidase activity [73]. Further COX-2-derived products can also regulate (up or down) NOS-2 expression levels and activity depending on the cell-type and experimental paradigm studied [74][75][76]. Hence, the heterogeneity of NOS-2 and COX-2 astrocyte expression in brain, as well as their coordinate regulation, could contribute to the establishment and maintenance of a network of communication among neurons and glia under both physiological and pathophysiological conditions in ways we have yet to understand fully.…”
Section: Discussionmentioning
confidence: 99%